(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The memoirs “As at the edge of the abyss” by Leonid Korenevych are original work not only about their lives but the memoirs that present generation of 60-ies as characters who recreated the fate of those ones associated with Ukrainian national revival of the 1960s and analysis of their ideology. Author’s image created in recollection impresses by harmony and integrity rising above the events that take place in the memoirs.